Association between medical comorbidities at diagnosis and paediatric acute lymphoblastic leukaemia and lymphoblastic lymphoma outcomes: protocol for a systematic review - Ernest K Amankwah; Maua Mosha; Jennifer Dean; Jennifer Mayer (BMJ Open)
Introduction Medical comorbidity at diagnosis is associated with treatment outcome in cancer. The aim of this project is to synthesise the evidence on the association between medical comorbidities and paediatric acute lymphoblastic leukaemia and lymphoblastic lymphoma outcomes.Methods and analysis A systematic review of the literature will be conducted by developing a search strategy that will combine medical subject headings and natural language key words related to acute lymphoblastic leukaemia or lymphoma, medical comorbidities and treatment-related outcomes. We will search MEDLINE and EMBASE to identify studies in human subjects and written in English from the inception of each database to 30 September 2022. Two authors will independently screen the titles and abstracts of retrieved studies based on the inclusion and exclusion criteria to identify potentially eligible studies. Full-text articles of eligible studies and final included articles will be retrieved and reviewed in a similar manner by two independent reviewers. Data extraction from included articles will be conducted independently by two authors using a standardised data extraction form. Risk of bias in the included studies will be assessed using existing relevant tools. A narrative and tabular summary of the data, including outcomes, will be provided if the data do not warrant a meta-analysis. If a meta-analysis is feasible, we will pool all the effect estimates. Heterogeneity among study effect sizes will be tested with Cochran’s Q test and quantified by the I2 statistic.Ethics and dissemination This study will not include the collection of original data, but it will be a summary of aggregate existing data. Thus, ethics approval is not applicable. The findings of the study will be disseminated through peer-reviewed publications.PROSPERO registration number CRD42022366669.